Making British And American Culture And Civilization Classes Engaging And Enjoyable - Raouti, Rabha (جامعة الوادي - University of Eloued, 2023)
ملخص يتناول هذا المقال التحديات التي تواجه طلاب السنة الأولى في جامعة سعيدة الذين يدرسون الثقافة والحضارة البريطانية والأمريكية لأول مرة. وتتعرض الورقة للموقف السلبي الذي يتبناه الطلاب تجاه هذه الدورة، وكيف يمكن للمدرسين تخفيف الضغط النفسي الذي يعاني منه الطلاب في هذه الفصول، بالإضافة إلى الطرق التي يمكن استخدامها لجعل الحصة أكثر جاذبية ومتعة. تم الاعتماد في هذا البحث على خبرة الباحث في تدريس الثقافة والحضارة في قسم اللغة الإنجليزية، وقد كشفت النتائج عن عدة عوامل متعددة الأوجه ترتبط بفشل هذه الوحدة، بعضها يتعلق بالموضوع نفسه، والبعض الآخر يعود إلى نقص المعرفة الخلفية للطلاب القادمين من المدارس الثانوية. وخلص الباحث إلى توصيات تؤكد على استخدام التعلم النشط لتوليد الحماس داخل الفصل من خلال استخدام أساليب التدريس المختلفة ودمج التكنولوجيا، والابتعاد عن الأساليب التقليدية التي تعتمد على الحفظ والأساليب التدريسية القديمة . Abstract: The purpose of this article is to highlight the challenges encountered by L1 EFL students at the University of Saida who encounter British and American culture and civilization for the first time. It delves into the negative attitude that students have towards this course and examines the teacher’s role in alleviating the stress experienced by students in these classes. Furthermore, it investigates ways to make the course more engaging and enjoyable. In this work, I draw on my teaching experience in culture and civilization at the department of English which spans over from 2007 to this time. The results revealed several multifaceted factors associated with the failure of this module. Some of these factors pertain to the subject matter itself, while others are due to the inadequate background knowledge of students who come from high school. The researcher concluded this study by proposing recommendations that emphasize active learning to generate enthusiasm in the classroom. This can be accomplished by utilizing different teaching approaches, incorporating technology, and moving away from conventional methods that rely on memorization and outdated teaching styles
A Case Study Of L1 Efl Students At The University Of Saida
مقال
Keywords: civilization; EFL teaching; negative attitudes; active learning; ICT; الحضارة ، التدريس ، المواقف السلبية ، التعلم النشط ، تكنولوجيا المعلومات والاتصالات